[PP.LB02.11] EGG WHITE HYDROLYSATE PREVENTS VASCULAR DYSFUNCTION AND THE INCREASED BLOOD PRESSURE CAUSED BY CHRONIC ALUMINUM EXPOSURE IN RATS. (September 2016) - Martinez, C.; Piagette, J.; Escobar, A.; Vassallo, D.; Peçanha, F.; Jiménez, E.; Miguel, M.; Wiggers, G.
Abstract : Objective: To investigate the effects of egg white protein hydrolysate (EWH), obtained after enzymatic hydrolysis with Pepsin, on vascular effects caused by chronic Aluminum (Al) exposure. Design and method: 32 three-month-old male Wistar rats were divided into four groups and treated orally for 42 days: a) Control - ultrapure water; b) AlCl3 - 100 mg/kg bw (Basic & Clin Pharm & Toxicol 105: 98–104, 2009); c) Hydrolysate - 1 g/kg/day of EWH (Food Chem 104:163–168, 2007); d) Hydrolysate plus Aluminum. Systolic blood pressure (SBP) was measured by plethysmography. Vascular function was studied in aortic and mesenteric resistance arteries (MRA) in isolated organ bath (J Pharmacol Exp Ther 321: 381–388, 2007 and Circ Res 41:19–26, 1977). Concentration-response curves to acetylcholine and sodium nitroprusside were performed. Vasoconstrictor response to phenylephrine (PHE) in presence and absence of endothelium and in presence of NOS inhibitor (L-NAME), potassium channels blocker (TEA), NAD(P)H oxidase inhibitor (apocynin), superoxide dismutase (SOD), non-selective COX inhibitor (indomethacin), selective COX-2 inhibitor (NS 398), and AT1 selective receptor blocker (losartan), were analyzed. Systemic and vascular reactive oxygen species (ROS), lipid peroxidation and antioxidant capacity were measured. Results were expressed as mean and SEM, compared by t–test and ANOVA followed by Bonferroni test (P < 0.05). Ethics Committee Approval 028/2014 - Unipampa. Results: EWH prevented: a) the increased SBP observed after Al exposure (Ct: 117. 2 ± 1.09; Al: 132.4 ± 5.20*; Hydrolysate: 117.6 ± 3.12#; Hydrolysate + Al: 118.4 ± 1.93# mmHg, n = 8 * vs Ct; #vs Al); b) the endothelial relaxation dysfunction; c) the increased vasoconstrictor response to PHE; d) restored the endothelium vasoconstrictor – modulation, nitric oxide bioavailability and potassium channels involvement; e) prevented the increased ROS production from NAD(P)H oxidase and contractile prostanoids from COX-2; f) inhibited the increased plasmatic and aortic ROS production and lipid peroxidation as well as the imbalance on antioxidant capacity after Al exposure. Conclusions: The EWH seems to be able to counteract the vascular toxic effects of AlCl3. Which points to a possible therapeutic effects based on functional food against a highly widespread environmental contaminant.